INFLUENCE OF PROGRAMMED SWIMMING ON SWIMMERS RESPIRATORY STATUS - Dejan Madić; Tomislav Okičić (Sport Mont, 2006)
The aim of research was to estimate influence of swimming on increasing of respiratory status at swimmers. Duration of training process was six months. The sample of variables of respiratory system was consisted of: forced vital capacity, forced expiratory volume in first second, summed expiratory flume on one half of VC, summed expiratory flume on one quarter, working expiratory flume and elasticity of thorax. Influence of swimming on all parameters of respiratory system is noticed